Comparative Study of C-arms for Intraoperative 3-dimensional Imaging and Navigation in Minimally Invasive Spine Surgery Part I: Applicability and Image Quality. Issue 6 (July 2017) - Klingler, Jan-Helge; Sircar, Ronen; Scheiwe, Christian; Kogias, Evangelos; Volz, Florian; Krüger, Marie T.; Hubbe, Ulrich
Abstract : Study Design: This was a retrospective analysis. Objective: This study compares 2 different 3-dimensional (3D) C-arm devices for intraoperative imaging and navigation with regard to clinical applicability and image quality. Summary of Background Data: Minimally invasive spine surgery requires intraoperative imaging techniques to adequately visualize the unexposed spine. For this purpose, mobile 3D C-arms became available along with the evolution of intraoperative navigation techniques. Methods: The C-arm devices Siremobil Iso-C 3D (Siemens) and Vision FD Vario 3D (Ziehm) perform an automated orbital rotation around the patient acquiring a 3D image set out of multiple successive fluoroscopic images. We report on technical specifications of the C-arms and our daily experience regarding clinical applicability. Furthermore, 5 spine surgeons evaluated blinded triplanar planes of 40 cervical, thoracic, and lumbar 3D scans that were obtained during routine surgery regarding usability for navigation. We assessed the delineation of cortical bone, artifacts, and overall image quality using a 0–10 numeric rating scale. Results: The Siremobil Iso-C 3D requires 128 seconds for its 190-degree scanning arc with equidistant isocenter. The Vision FD Vario 3D performs an elliptical scanning arc and completes its 135-degree scan in 64 seconds; furthermore, it features a flat panel detector and fully digital imaging. The smaller dimensions of the Vision FD Vario 3D made it easier to maneuver in the operating room compared with the more bulky Siremobil Iso-C 3D. With respect to image quality in cervical 3D scans, the Siremobil Iso-C 3D reached significantly higher scores in all categories. The Vision FD Vario 3D revealed less artifacts in lumbar 3D scans. Conclusions: The Siremobil Iso-C 3D provides high-quality 3D scans in slender spine regions (eg, cervical spine), whereas the Vision FD Vario 3D appears to have advantages in the lumbar spine. Further evolution and novel devices are needed to optimize image quality and handling.